PENGARUH PEMBERIAN KIRINYU (CHROMOLAENA ODORATA) SEBAGAI SUMBER BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS CABAI BESAR (CAMPSICUM ANNUM) - Fowo, Kristono Yohane; Murdaningsih, Murdaningsih; Lanamana, Willybrordus (AGRICA, 2010)
This study aims to determine the effect of giving Kirinyu (Chromolaena odorata) as a source of organic matter on growth and yield of two varieties of Chilli (Capsicum annum), and to determine the optimum dose Kirinyu that can improve crop growth and yield of the Big Chilli, research was conducted in the Garden University College of Agriculture experiment Flore, Village Lokoboko, District Ndona, Ende with ± 500 meters altitude above sea level, starting in September 2010-April 2011. The design used in this study is the Group Randomized Factorial Design with the treatment, the first factor (V), and Varieties Amando (V2), and the second factor (K) is the dose of organic material Kirinyu namely K0 (without Kirinyu), K1 (Kirinyu10 tons/ha), K2 (Kirinyu 15 tons/ha), K3 (Kirinyu20 tonnes/ha). Variable observation in this study was ?Higher Plants, Number of Leaves, Leaf Area, Total Fruit, Fruit diameter and weight of fruit per plant?. The results showed that administration of doses as a source of organic material Kirinyu significant effect on the varieties (V) and different doses Kirinyu to Total Leaf, Leaf Area observations at age 42 days after transplanting (DAT), and also significantly influenced Number of  Fruit, Fruit Weight, and fruit diameter. Use of Hot Beauty varieties has increased to Total Leaf (21.67 strands), number of fruits (31.00 fruits), and fruit weight (279.00 grams) and more resistant to high rainfall intensity, and for variety  Amando has increased to broad leaves (187.02 cm), and fruit diameter (1.74 cm) and not resistant to rain intensity. But for Kirinyu dose also significantly influenced leaf number, leaf area at the age of 42 observation days after transplanting (DAT), and also significantly influenced fruit number, fruit weight and fruit diameter. Chili optimum plant growth is shown in the use Kirinyu a dose of 20 tonnes/ha ie number of leaves (19.23 strands), leaf area (208.25 cm), number of fruits (41.58), fruit weight (7.44 grams), fruit diameter (1.66 cm).